Two-step single-reactor synthesis of oleic acid- or undecylenic acid-stabilized magnetic nanoparticles by thermal decomposition - Nahorniak, Mykhailo; Pasetto, Pamela; Greneche, Jean-Marc; Samaryk, Volodymyr; Auguste, Sandy; Rousseau, Anthony; Nosova, Nataliya; Varvarenko, Serhii (Beilstein Journal of Nanotechnology, 2023)
Different iron oxides (i.e., magnetite, maghemite, goethite, wüstite), particularly nanosized particles, show distinct effects on living organisms. Thus, it is of primary importance for their biomedical applications that the morphology and phase-structural state of these materials are investigated. The aim of this work was to obtain magnetic nanoparticles in a single reactor using Fe(III) acetylacetonate as the initial precursor for the synthesis of Fe(III) oleate or Fe(III) undecylate followed by their thermolysis in situ. We proposed a new approach, according to which the essential magnetite precursor (a complex salt of higher acids – Fe(III) alkanoates) is obtained in a solvent with a high boiling point via displacement reaction of acetylacetone with a higher acid from Fe(III) acetylacetonate during its elimination from the reaction mixture under vacuum conditions. Magnetic nanoparticles (NPM) were characterized in terms of morphology, hydrodynamic diameter, and composition via several techniques, such as transmission electron microscopy, dynamic light scattering, thermogravimetric analysis, Fourier-transform infrared spectroscopy/attenuated total reflectance, 57Fe Mössbauer spectroscopy, and X-ray diffraction. The effect of unsaturated oleic (OA) and undecylenic (UA) acids, which are both used as a reagent and as a nanoparticle stabilizer, as well as the influence of their ratio to Fe(III) acetylacetonate on the properties of particles were investigated. Stable dispersions of NPM were obtained in 1-octadecene within the OA or UA ratio from 3.3 mol to 1 mol of acetylacetonate and up to 5.5 mol/mol. Below the mentioned limit, NPM dispersions were colloidally unstable, and at higher ratios no NPM were formed which could be precipitated by an applied magnetic field. Monodisperse nanoparticles of iron oxides were synthesized with a diameter of 8–13 nm and 11–16 nm using OA and UA, respectively. The organic shell that enables the particle to be dispersed in organic media, in the case of oleic acid, covers their inorganic core only with a layer similar to the monomolecular layer, whereas the undecylenic acid forms a thicker layer, which is 65% of the particle mass. The result is a significantly different resistance to oxidation of the nanoparticle inorganic cores. The core of the particles synthesized using oleic acid is composed of more than 90% of maghemite. When undecylenic acid is used for the synthesis, the core is composed of 75% of magnetite.
Keywords: Fe(III) acetylacetonate; iron oxide nanoparticles; maghemite; magnetic nanoparticles; magnetite; thermal decomposition synthesis